Light-dependent expression of flg22-induced defense genes in Arabidopsis - Sano, Satoshi; Aoyama, Mayu; Nakai, Kana; Shimotani, Koji; Yamasaki, Kanako; Sato, Masa H.; Tojo, Daisuke; Suwastika, I. Nengah; Nomura, Hironari; Shiina, Takashi (Frontiers in Plant Science, 2014)
Chloroplasts have been reported to generate retrograde immune signals that activate defense gene expression in the nucleus. However, the roles of light and photosynthesis in plant immunity remain largely elusive. In this study, we evaluated the effects of light on the expression of defense genes induced by flg22, a peptide derived from bacterial flagellins which acts as a potent elicitor in plants. Whole-transcriptome analysis of flg22-treated Arabidopsis thaliana seedlings under light and dark conditions for 30 min revealed that a number of (30%) genes strongly induced by flg22 (>4.0) require light for their rapid expression, whereas flg22-repressed genes include a significant number of genes that are down-regulated by light. Furthermore, light is responsible for the flg22-induced accumulation of salicylic acid, indicating that light is indispensable for basal defense responses in plants. To elucidate the role of photosynthesis in defense, we further examined flg22-induced defense gene expression in the presence of specific inhibitors of photosynthetic electron transport: 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) and 2,5-dibromo-3-methyl-6-isopropyl-benzoquinone (DBMIB). Light-dependent expression of defense genes was largely suppressed by DBMIB, but only partially suppressed by DCMU. These findings suggest that photosynthetic electron flow plays a role in controling the light-dependent expression of flg22-inducible defense genes.